Limnophyes knispelae sp. n. and L. sartorii sp. n., two new crenophilous species from the Swiss Alps (Chironomidae, Orthocladiinae) - Joel Moubayed; Brigitte Lods-Crozet (CHIRONOMUS Journal of Chironomidae Research, 2023)
Limnophyes knispelae sp. n and L. sartorii sp. n. are diagnosed and described based on material collected in the high Alpine valley of the Rhône river and the cirque of Macun in the Swiss National Park (alt. 1800-2616 m a.s.l.). The first new species is described only as male adult, while the second as male adult and pupal exuviae. Main distinguishing characters found in the male adult of L. knispelae sp. n. L. sartorii sp. n. are: clypeus shield-like shaped; humeral pit typically circular with 3-4 or 9 lanceolate setae; virga strong spine-like; preepisternals vary from 4-6 to 4-8. The pupal exuviae of L. sartorii sp. n. is characterized by having frontal apotome domed; thoracic horn reduced to nose-like tubercle; posterior area of tergites II-VI with 1-7 rows of minute hooks; segment VIII with 5 lateral setae; inner posterior margin of anal lobe straight.